A new challenge for urban planning in Turkey: socio-spatial impacts of forced migration - Levent, Tolga (European Spatial Research and Policy, 2019)
In recent decades, forced migration has become a globally salient issue for both developed and developing countries. As a developing country, Turkey is a significant destination for forced migration, with more than 3.6 million Syrian immigrants. This study concentrates on the socio-spatial impacts of forced migration in Turkish cities where Syrian immigrants have been concentrated and aims to answer the question: “Does forced migration produce an urban crisis in such cities?” The study leads to a prescription about new qualities of urban planning for coping with the urban crisis through a resilience strategy.